Toxic Shock Syndrome: Characterization of Human Immune Responses to TSST-1 and Evidence for Sensitivity Thresholds - Kimber, Ian; Nookala, Suba; Davis, Catherine C.; Gerberick, G. Frank; Tucker, Heidi; Foertsch, Leslie M.; Dearman, Rebecca J.; Parsonnet, Jeffrey; Goering, Richard V.; Modern, Paul; Donnellen, Meghan; Morel, Jorge; et al. (Toxicological sciences, 2013)
Noninvasive vaginal infections by Staphylococcus aureus strains producing the superantigen TSST-1 can cause menstrual toxic shock syndrome (mTSS). With the objective of exploring the basis for differential susceptibility to mTSS, the relative responsiveness to TSST-1 of healthy women has been investigated. Peripheral blood mononuclear cells from healthy donors were incubated with purified TSST-1 or with the T-cell mitogen phytohemmaglutinin (PHA), and proliferation was measured. The concentrations of TSST-1 and PHA required to elicit a response equivalent to 15% of the maximal achievable response (EC15) were determined. Although with PHA, EC15 values were comparable between donors, subjects could be classified as being of high, medium, or low sensitivity based on responsiveness to TSST-1. Sensitivity to TSST-1-induced proliferation was associated with increased production of the cytokines interleukin-2 and interferon-γ. When the entire T lymphocyte population was considered, there were no differences between sensitivity groups with respect to the frequency of cells known to be responsive to TSST-1 (those bearing CD3(+) Vβ2(+)). However, there was an association between sensitivity to TSST-1 and certain HLA-class II haplotypes. Thus, the frequencies of DR7DQ2, DR14DQ5, DR4DQ8, and DR8DQ4 haplotypes were greater among those with high sensitivity, a finding confirmed by analysis of responses to immortalized homozygous B cell lines. Collectively, the results reveal that factors other than neutralizing antibody and the frequency of Vβ2(+) T lymphocytes determine immunological responsiveness to TSST-1. Differential responsiveness of lymphocytes to TSST-1 may form the basis of interindividual variations in susceptibility to mTSS.